2017
DOI: 10.18488/journal.70.2017.43.63.76
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Maize Productivity (Zea Mays L.) by Mycorrhizal Inoculation on Ferruginous Soil in Center of Benin

Abstract: The objective of our study was to evaluate the promoted effects of three arbuscular mycorrhizal fungi (AMF) on maize growth and yield on ferruginous soil in center of Benin. The maize variety used was EVDT 97 STR C1. The maize seeds were inoculated with each of three arbuscular mycorrhizal fungi (Glomus intraradices, Funneliformis mosseae and Rhizophagus cubens) combined with or not to mineral fertilizer dose recommended (50% of NPK). The experimental device was a completely randomized random block of nine tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…During the experimentation, mycorrhiza significantly influenced the leaf area and stem girth of the plant. A positive effect of mycorrhizal application on plant growth parameter had earlier been reported [17].…”
Section: The Soil's Physical and Chemical Characteristicsmentioning
confidence: 69%
“…During the experimentation, mycorrhiza significantly influenced the leaf area and stem girth of the plant. A positive effect of mycorrhizal application on plant growth parameter had earlier been reported [17].…”
Section: The Soil's Physical and Chemical Characteristicsmentioning
confidence: 69%
“…In addition, the soils of Central Benin have an organic matter rate of 1.16% and a pH in water (6.2) allowing a good expression of R. intraradices, which shows a good colonization of plant roots in soils with a pH between 7 and 7.6. Rivera et al (2003) in Cuba, Assogba et al (2017), andAguégué et al (2021) in Benin also observed a 35-50% increase in maize yields compared with the control (without AMF or mineral fertilizers) following the application of N 15 P 15 K 15 _Urea, which created a commercial strain. It should be noted that other factors such as temperature and pest attacks may explain the differences in yield observed from one area to another.…”
Section: Discussionmentioning
confidence: 99%